2021
DOI: 10.3390/pharmaceutics13081160
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-Radiolabeling and Pharmacological Characterization of a Kit-Based Formulation of the Gastrin-Releasing Peptide Receptor (GRP-R) Antagonist RM2 for Convenient Preparation of [68Ga]Ga-RM2

Abstract: Background: [68Ga]Ga-RM2 is a potent Gastrin-Releasing Peptide-receptor (GRP-R) antagonist for imaging prostate cancer and breast cancer, currently under clinical evaluation in several specialized centers around the world. Targeted radionuclide therapy of GRP-R-expressing tumors is also being investigated. We here report the characteristics of a kit-based formulation of RM2 that should ease the development of GRP-R imaging and make it available to more institutions and patients. Methods: Stability of the inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The radioligands used in this study, their respective targets and their affinities towards the target are summarized as follows: [ 111 In]In-PSMA-617 targets PSMA (Ki = 2.34 ± 2.94 nM [ 14 ]), [ 111 In]In-RM2 targets GRP-R (Kd = 2.9 ± 0.4 nM [ 15 ], [ 111 In]In-JMV 6659 is a radioligand of NTS 1 (Kd = 6.29 ± 1.37 nM [ 16 ]), [ 111 In]In-JMV 7488 is a radioligand of NTS 2 (Kd = 36.39 ± 4.02 nM) [ 17 ], [ 177 Lu]Lu-DOTATATE targets SST 2 (Kd = 2.0 ± 0.8 nM [ 18 ]) and [ 67 Ga]Ga-pentixafor is a radioligand of CXCR4 (Kd = 24.6 ± 2.5 nM [ 19 ]). The production and control of the radiopharmaceuticals used are described in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…The radioligands used in this study, their respective targets and their affinities towards the target are summarized as follows: [ 111 In]In-PSMA-617 targets PSMA (Ki = 2.34 ± 2.94 nM [ 14 ]), [ 111 In]In-RM2 targets GRP-R (Kd = 2.9 ± 0.4 nM [ 15 ], [ 111 In]In-JMV 6659 is a radioligand of NTS 1 (Kd = 6.29 ± 1.37 nM [ 16 ]), [ 111 In]In-JMV 7488 is a radioligand of NTS 2 (Kd = 36.39 ± 4.02 nM) [ 17 ], [ 177 Lu]Lu-DOTATATE targets SST 2 (Kd = 2.0 ± 0.8 nM [ 18 ]) and [ 67 Ga]Ga-pentixafor is a radioligand of CXCR4 (Kd = 24.6 ± 2.5 nM [ 19 ]). The production and control of the radiopharmaceuticals used are described in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…This has to be optimized finely to prevent saturation of targeted receptors with unlabeled biomolecule. On the other hand, this, plus shorter production time and higher radiolabeling yield with the kit than with automated module synthesis, might allow for multiple patient preparations, although kits are usually recommended as single-dose preparations ( 118 , 124 , 125 ). Regarding outcomes of both processes, in terms of product characteristics, quality control gave comparable results ( Figure 6A ), and both methods are reliable and comply with Good Manufacturing Practices and European Pharmacopeia specifications ( 113 , 124 , 126 , 127 ).…”
Section: Cold Kitsmentioning
confidence: 99%
“…It should be noted that a commercial kit would be more expensive. In a study on [ 68 Ga]Ga-RM2 synthesis, consumable costs for a synthesis was reported to be 282.1 vs. 65.7 € for a module and a kit, respectively, whereas the shorter production time and higher radiolabeling yield with the kit would allow for the injection of at least two additional patients ( 125 ). This gain in production time may also improve patient workflow, improving, again, cost efficiency.…”
Section: Cold Kitsmentioning
confidence: 99%
See 1 more Smart Citation
“…A K D value of 1.9 ± 1.2 nM toward the GRPR was obtained on PC3 cells, and a value of 17.7 ± 4.9 nM toward the PSMA was obtained on 22Rv1 cells (22Rv1 expresses a small amount of GRPR; in this case, the GRPR interaction was blocked by coincubation with 10 μM of bombesin). The affinity of [ 68 Ga]Ga-18 toward the GRPR and the PSMA was lower than GRPR-and PSMAtargeting standards such as [ 68 Ga]Ga-RM2 (K D = 0.3 ± 0.2 nM on PC3 cells) 42 and [ 68 Ga]Ga-PSMA-617 (K i = 2.3 ± 2.9 nM on LnCaP cells) 43 but still in the nanomolar range. 43 To assess [ 68 Ga]Ga-18 in vivo, a model of athymic nude mice doubly xenografted with PC3 cells on the left shoulder and 22Rv1 cells on the right shoulder was used.…”
mentioning
confidence: 93%